FET668 : Asian aesthetic 2 / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
This course introduces studies on art aesthetics from major Asian traditions such as Hinduism, Buddhism (Confucianism &Taoism), and Zen. It covers, among others, the theory of Rasa, the Confucian concept of jen, Li na Chin; the Tao i-ching, and the wabi sabi of the Zen. The conception that many aesthetic studies from Asian regions proceed on the assumption that a higher realm of Being exists that transcends empirical phenomena and the integration of art with life will be the main topic of discussion in this program.